Gene coexpression network analysis of oil biosynthesis in an interspecific backcross of oil palm. (19th July 2016) - Guerin, Chloé; Joët, Thierry; Serret, Julien; Lashermes, Philippe; Vaissayre, Virginie; Agbessi, Mawussé D. T.; Beulé, Thierry; Severac, Dany; Amblard, Philippe; Tregear, James; Durand‐Gasselin, Tristan; Morcillo, Fabienne; et al.
Summary: Global demand for vegetable oils is increasing at a dramatic rate, while our understanding of the regulation of oil biosynthesis in plants remains limited. To gain insights into the mechanisms that govern oil synthesis and fatty acid (FA) composition in the oil palm fruit, we used a multilevel approach combining gene coexpression analysis, quantification of allele‐specific expression and joint multivariate analysis of transcriptomic and lipid data, in an interspecific backcross population between the African oil palm, Elaeis guineensis, and the American oil palm, Elaeis oleifera, which display contrasting oil contents and FA compositions. The gene coexpression network produced revealed tight transcriptional coordination of fatty acid synthesis (FAS) in the plastid with sugar sensing, plastidial glycolysis, transient starch storage and carbon recapture pathways. It also revealed a concerted regulation, along with FAS, of both the transfer of nascent FA to the endoplasmic reticulum, where triacylglycerol assembly occurs, and of the production of glycerol‐3‐phosphate, which provides the backbone of triacylglycerols. Plastid biogenesis and auxin transport were the two other biological processes most tightly connected to FAS in the network. In addition to WRINKLED1, a transcription factor (TF) known to activate FAS genes, two novel TFs, termed NF‐YB‐1 and ZFP‐1, were found at the core of the FAS module. The saturated FA content of palm oil appeared to vary above all in relation to the level of transcripts of the gene coding for β‐ketoacyl‐acyl carrier protein synthase II. Our findings should facilitate the development of breeding and engineering strategies in this and other oil crops. Significance Statement: Global demand for vegetable oils is increasing, but our understanding of how oil biosynthesis is regulated remains limited. Here we used an interspecific backcross population of oil palm, transcript coexpression and transcript–metabolite correlations to identify novel enzymes, transcription factors and cellular processes involved in oil biosynthesis. Our findings should facilitate the development of novel breeding and engineering strategies in oil palm and other oil crops.